Application of microbial fuel cell technology for vinasse treatment and bioelectricity generation - Ottoni, C. (2019)
Our study evaluated the performance of different two-chambered microbial fuel cell (MFC) prototypes, operated with variable distance between electrodes and Nafion membrane and specific inoculum concentration, applied for vinasse treatment.